Electrochemical devices and electronic devices
Patent Information
- Application Number
- CN202280006004.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-21
AI Technical Summary
现有的粘结剂结晶度和固化交联度高,刚性强不易发生变形,折弯时产生较大内应力容易造成极片开裂,难以适应弧形电池的应用要求
[0007]本申请的实施例中粘结剂包括粘结高分子和热塑性高分子,因此粘结剂为具有塑性的粘结剂,粘结剂中的分子链具有良好的移动能力,极片随着弯曲成弧形,曲率高的部位发生应力集中,粘结剂通过塑性变形吸收能量,避免界面失粘、极片开裂问题,同时,粘结剂产生永久变形量,限制弧度回弹率,从而获得曲率更高的弧形。本申请提供的粘结剂通过粘结高分子的锚固作用,保证粘接强度,同时添加塑性好、弹性小的热塑性高分子作为增塑剂,提供发生永久变形的能力,能够使弧形电化学装置的弧度回弹率降低,极片具有良好的加工性,弧形极片的曲率半径达到5mm至200mm仍具有良好的循环性能。
Smart Images

Figure CN116261796B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical energy storage, and more particularly to electrochemical devices and electronic devices. Background Technology
[0002] With the development and advancement of electrochemical devices (such as lithium-ion batteries and sodium-ion batteries), the demand for curved electrochemical devices is constantly increasing. During the manufacturing and use of curved electrochemical devices, the adhesion performance between the active material layer of the electrode and the current collector under high curvature, as well as the stability of the electrode's curvature, significantly affect the cycle performance and rate performance of the electrochemical device. Existing binders have high crystallinity and curing cross-linking degree, are rigid and not easily deformed, and generate significant internal stress during bending, which can easily cause electrode cracking, making them unsuitable for the application requirements of curved batteries. Summary of the Invention
[0003] Some embodiments of this application propose an electrochemical device comprising an electrode, which includes a current collector and an active material layer located on at least one side of the current collector. The active material layer comprises an active material and a binder, the binder comprising a bonding polymer and a thermoplastic polymer. The radius of curvature R of the electrode is 5 mm to 200 mm. The molecular chains in the binder have good mobility, allowing the electrode to bend into an arc shape with the electrochemical device. Stress concentration occurs at areas with high curvature. The binder absorbs energy through plastic deformation, avoiding interfacial debonding and electrode cracking. Simultaneously, the amount of permanent deformation generated by the binder can limit the curvature rebound rate, thereby obtaining an arc-shaped electrode with better curvature. In this application, the binder ensures bonding strength through the anchoring effect of the bonding polymer and provides the ability to undergo permanent deformation through the use of a thermoplastic polymer with good plasticity and low elasticity as a plasticizer. This reduces the curvature rebound rate of the arc-shaped electrode, giving it good processability. When the radius of curvature of the electrode is in the range of 5 mm to 200 mm, the electrochemical device exhibits good cycle performance.
[0004] In some embodiments, the radius of curvature R of the electrode is 25 mm to 100 mm, thereby meeting the requirements for curved electrodes and preventing desorption of the active material layer from the current collector. In some embodiments, the thermoplastic polymer includes at least one of polyethylene, polypropylene, polyvinyl chloride, polycarbonate, dendritic polyamide amine, ethylene vinyl acetate copolymer, hyperbranched acrylic acid, or hyperbranched acrylate. In some embodiments, the crystallinity of the thermoplastic polymer is less than 50%, thereby preventing excessive stiffness. In some embodiments, the weight-average molecular weight of the thermoplastic polymer is 5,000 to 80,000, thereby ensuring processability. In some embodiments, the elongation at break of the thermoplastic polymer is 100% to 500%, thereby preventing the curvature of the electrode from rebounding.
[0005] In some embodiments, the bonding polymer comprises at least one selected from polyvinylidene fluoride, styrene-butadiene emulsion, carboxymethyl cellulose, polyaniline, polyacrylic acid, alginate, guar gum, gum arabic, xanthan gum, gelatin, chitosan, β-cyclodextrin, polyethyleneimine, polyimide, or waterborne epoxy resin. In some embodiments, the thermoplastic polymer comprises 0.5% to 50% by mass of the binder, based on the total mass of the binder, thereby ensuring both plasticity and adhesive strength. In some embodiments, the electrode is a positive electrode, and the thermoplastic polymer comprises 0.5% to 10% by mass of the binder. In some embodiments, the electrode is a negative electrode, and the thermoplastic polymer comprises 1% to 50% by mass of the binder, thereby adapting to the positive electrode and ensuring the adhesive strength of the binder while possessing sufficient plasticity. In some embodiments, the tensile permanent deformation of the binder is 50% to 100%, indicating good plasticity.
[0006] Embodiments of this application also provide an electronic device including the electrochemical device described above.
[0007] In the embodiments of this application, the binder includes bonding polymers and thermoplastic polymers. Therefore, the binder is a plastic binder with good molecular chain mobility. As the electrode is bent into an arc shape, stress concentration occurs in areas with high curvature. The binder absorbs energy through plastic deformation, avoiding interfacial debonding and electrode cracking. At the same time, the binder generates permanent deformation, limiting the curvature rebound rate, thereby obtaining an arc shape with higher curvature. The binder provided in this application ensures bonding strength through the anchoring effect of bonding polymers, while adding thermoplastic polymers with good plasticity and low elasticity as plasticizers provides the ability to undergo permanent deformation. This reduces the curvature rebound rate of the arc-shaped electrochemical device, giving the electrode good processability. The arc-shaped electrode maintains good cycle performance even with a curvature radius of 5mm to 200mm. Attached Figure Description
[0008] The above and other features, advantages, and aspects of the embodiments of this disclosure will become more apparent from the accompanying drawings and the following detailed description. Throughout the drawings, the same or similar reference numerals denote the same or similar elements. It should be understood that the drawings are schematic, and the originals and elements are not necessarily drawn to scale.
[0009] Figure 1 This is a schematic diagram of an electrochemical device.
[0010] Figure 2 This is a schematic diagram of the composition of an adhesive and a schematic diagram of the adhesive under stress. Detailed Implementation
[0011] The following embodiments are intended to enable those skilled in the art to fully understand this application, but do not limit this application in any way.
[0012] With continuous technological advancements, the demand for arc-shaped electrochemical devices capable of curvature bending is constantly increasing. During the manufacturing and use of arc-shaped electrochemical devices, the adhesion performance between the active material layer and the current collector under high curvature, as well as the arc stability of the electrode, significantly impacts the cycle performance and rate performance of the electrochemical device. Existing binders have high crystallinity and curing cross-linking degree, resulting in high rigidity and resistance to deformation. However, the large internal stress generated during bending easily leads to electrode cracking, making them unsuitable for the application requirements of arc-shaped batteries. Some technologies increase the flexibility of the active material bonding layer by reducing crystallinity, achieving a flexible effect. For arc-shaped electrodes, in addition to improving the adhesion and flexibility of the bonding layer, it is also necessary to further control the plasticity of the bonding layer to prevent the arc rebound after bending.
[0013] Curve rebound is closely related to the mechanical properties of the electrode material itself and the stress concentration during bending. Currently, most methods to suppress curve rebound involve adding external force constraints during the encapsulation stage, achieved through a steel shell or by increasing the ductility of the packaging bag. This approach increases manufacturing costs and is not conducive to thinning of electrochemical devices. The binder in the electrode, as the main additive connecting the electrodes, not only ensures the integrity of the electrodes but also significantly affects the stability and cycle performance of the battery.
[0014] In some embodiments of this application, an electrochemical device is proposed. This electrochemical device may be, for example, a lithium-ion battery, a sodium-ion battery, etc. The electrochemical device includes electrodes. In some embodiments, please refer to... Figure 1 The electrochemical device may include a positive electrode 1, a separating membrane 2, and a negative electrode 3. The electrode may be either the positive electrode 1 or the negative electrode 3. The electrode includes a current collector and an active material layer located on at least one side of the current collector; the current collector may be made of copper foil or aluminum foil, and the active material layer includes an active material and a binder, the binder including a bonding polymer and a thermoplastic polymer, and the radius of curvature R of the electrode is from 5 mm to 200 mm. In the application, such as... Figure 2 As shown in (a), the adhesive comprises bonding polymer 4 and thermoplastic polymer 5, therefore the adhesive has plasticity, such as Figure 2As shown in (b), when the binder is subjected to an external force F, it undergoes irreversible deformation through molecular chain movement, exhibiting plasticity. The molecular chains in the binder possess excellent mobility, causing the electrode to bend into an arc shape with the electrochemical device. Stress concentration occurs in areas of high curvature. The binder absorbs energy through plastic deformation, preventing interfacial debonding and electrode cracking. Simultaneously, the plastic binder generates permanent deformation, limiting the curvature rebound rate, thus achieving an arc-shaped electrochemical device with better curvature. The binder provided in this application ensures bonding strength through the anchoring effect of the bonding polymer, while adding a thermoplastic polymer with good plasticity and low elasticity as a plasticizer, providing the ability to undergo permanent deformation. This reduces the curvature rebound rate of the arc-shaped electrochemical device, giving the electrode good processability and maintaining good cycle performance even with curvature radii ranging from 5 mm to 200 mm.
[0015] In this application, the binder includes both bonding polymers and thermoplastic polymers. Bonding polymers typically include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) emulsions, and carboxymethyl cellulose (CMC). If only bonding polymers are used, the high crystallinity of PVDF can cause damage to the crystal structure when the electrode is bent under external force, leading to cracks and making it easy for the active material layer to fall off the current collector. SBR emulsions have strong adhesion, but rubber-like polymers have high elasticity and can quickly recover from large deformations, making it difficult to maintain the stability of the arc. Carboxymethyl cellulose has a high elastic modulus and is brittle after curing. Arc-shaped batteries using CMC as a binder experience high internal stress after bending, easily causing stress concentration and electrode cracking, affecting battery performance. If only thermoplastic polymers are used as binders, the stress concentration problem during processing can be improved. However, thermoplastic polymers are mostly linear polymers with insufficient adhesion, making it difficult to ensure the integrity of the electrode. This application utilizes both bonding polymers and thermoplastic polymers in its binder. While ensuring adhesion, it enhances the plastic deformation capacity of the binder within the electrode, allowing the electrode to bend into an arc shape. Under high curvature, energy is absorbed through plastic deformation, hindering microcrack propagation and ensuring the integrity of the arc-shaped electrode, thus avoiding cracking and powder shedding. The thermoplastic polymer, acting as a plasticizer, gives the molecular chains in the binder excellent mobility, resulting in greater permanent deformation under bending stress on the electrode, reducing the curvature rebound of the arc-shaped electrode, and thereby improving the cycle performance of the electrochemical device. The thermoplastic polymer, as a plasticizer in the binder, increases the plastic deformation capacity of the binder, enabling the electrochemical device to achieve even higher curvature.
[0016] In some embodiments of this application, the radius of curvature R of the electrode is between 25 mm and 100 mm. The half-radius of curvature of the electrode characterizes the curvature of the electrode. The smaller the radius of curvature, the greater the curvature. If the radius of curvature is too small, it is easy to cause desorption between the active material layer and the current collector in the electrode. If the radius of curvature is too large, the curvature of the electrode is insufficient and may not meet the requirements. In this embodiment, the radius of curvature R of the electrode is between 25 mm and 100 mm, which can meet the requirements for the curved electrode and prevent the active material layer from desorbing from the current collector.
[0017] In some embodiments of this application, the thermoplastic polymer includes at least one selected from polyethylene, polypropylene, polyvinyl chloride, polycarbonate, dendritic polyamide amine, ethylene vinyl acetate copolymer, hyperbranched acrylic acid, or hyperbranched acrylate. In some embodiments, the ethylene vinyl acetate copolymer contains 15% to 40% vinyl acetate by mass.
[0018] In some embodiments of this application, the crystallinity of the thermoplastic polymer is less than 50%. In some embodiments, the crystallinity of the thermoplastic polymer affects its stiffness; excessively high crystallinity results in excessively high stiffness, which may lead to difficulty in deformation.
[0019] In some embodiments of this application, the weight-average molecular weight of the thermoplastic polymer is between 5,000 and 80,000. In some embodiments, the weight-average molecular weight is closely related to the performance and processing properties of the polymer material. If the relative weight-average molecular weight is too low, the mechanical strength and toughness of the material will be affected. If the weight-average molecular weight is too high, the melt viscosity of the polymer will increase, making processing and molding difficult.
[0020] In some embodiments of this application, the elongation at break of the thermoplastic polymer is between 100% and 500%. In some embodiments, if the elongation at break of the thermoplastic polymer is too low, the thermoplastic polymer may break during bending, affecting the flexibility of the electrode. If the elongation at break of the thermoplastic polymer is too high, the energy that the thermoplastic polymer can absorb during plastic deformation may be insufficient, which is not conducive to preventing the curvature rebound of the electrode.
[0021] In some embodiments of this application, the adhesive polymer includes at least one of polyvinylidene fluoride, styrene-butadiene emulsion, carboxymethyl cellulose, polyaniline, polyacrylic acid, alginate, guar gum, gum arabic, xanthan gum, gelatin, chitosan, β-cyclodextrin, polyethyleneimine, polyimide, or waterborne epoxy resin.
[0022] In some embodiments of this application, the mass percentage of thermoplastic polymer in the binder is 0.5% to 50% based on the total mass of the binder. In this embodiment, the mass percentage of thermoplastic polymer as a plasticizer in the binder is between 0.5% and 50%. Thermoplastic polymer has flexible molecular chain segments that deform through molecular chain extension and slippage. The binding polymer can coat or entangle the active material, acting as a bridge between the active material and the current collector, thus exhibiting the advantage of high adhesion. By adjusting the ratio of binding polymer and thermoplastic polymer, a composite binder is obtained that possesses both plasticity and adhesion. After being bent by external force, irreversible deformation occurs inside the electrode material, effectively suppressing the curvature rebound of the arc battery. The addition of thermoplastic polymer to the electrode can reduce the curvature rebound rate of the electrochemical device to 1% to 5%, and the electrode has good processability, maintaining good cycle performance even when the radius of curvature reaches 5mm to 200mm. If the mass percentage of thermoplastic polymers in the adhesive is too low, it may not provide sufficient plasticity to the adhesive; if the mass percentage of thermoplastic polymers in the adhesive is too high, it may result in insufficient adhesive strength.
[0023] In some embodiments of this application, the electrode is a positive electrode, and the mass percentage of thermoplastic polymer in the binder is 0.5% to 10%. In some embodiments, the mass percentage of thermoplastic polymer in the binder can differ between the positive and negative electrodes. This is because the active materials and binders used in the positive and negative electrodes may be different. The positive electrode generally exhibits stronger plasticity than the negative electrode. Therefore, the mass percentage of thermoplastic polymer in the binder of the positive electrode can be relatively higher than that in the binder of the negative electrode. This ensures that the positive and negative electrodes exhibit similar curvature rebound under the same degree of bending, avoiding misalignment between the positive and negative electrodes due to different curvature rebound. The mass percentage of thermoplastic polymer in the binder of the positive electrode is 0.5% to 10%, which ensures the adhesion of the binder while maintaining sufficient plasticity of the positive electrode.
[0024] In some embodiments of this application, the electrode is a negative electrode, and the thermoplastic polymer has a mass percentage content of 1% to 50% in the binder, thereby adapting to the positive electrode and ensuring the adhesive force of the binder while having sufficient plasticity.
[0025] In some embodiments of this application, the tensile permanent deformation of the adhesive is 50% to 100%. In some embodiments, the tensile permanent deformation of the adhesive is determined as follows: the adhesive is placed on a horizontal glass plate and allowed to dry naturally for 24 hours, then dried in a 60°C constant temperature oven to constant weight to obtain a film. This film is then cut into dumbbell-shaped standard samples using a dumbbell-shaped cutter. Tensile testing is performed using a universal electronic tensile testing machine. The film is held at 100% fixed elongation for 10 minutes, and the load is immediately released, allowing it to recover freely for 10 minutes. The residual deformation is measured, and the tensile permanent deformation is calculated. In this embodiment, the permanent deformation of the adhesive after 100% fixed elongation reaches 50%, indicating that the adhesive already possesses good plasticity and a small curvature rebound.
[0026] In some embodiments, the electrode is a positive electrode, the active material layer is a positive electrode active material layer, and the active material is a positive electrode material. In some embodiments, the positive electrode material includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium oxide phosphate, sodium vanadium oxide phosphate, lithium vanadium oxide, lithium vanadium oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium-rich manganese-based materials, or lithium nickel cobalt aluminum oxide. In some embodiments, the positive electrode active material layer may further include a conductive agent. In some embodiments, the conductive agent in the positive electrode active material layer may include at least one of conductive carbon black, Ketjen black, sheet graphite, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the mass ratio of the positive electrode material, conductive agent, and binder in the positive electrode active material layer may be (80 to 99):(0.1 to 10):(0.1 to 10). In some embodiments, the thickness of the positive electrode active material layer may be from 10 μm to 500 μm. It should be understood that the above description is merely an example, and the positive electrode active material layer of the positive electrode may use any other suitable material, thickness, and mass ratio.
[0027] In some embodiments, the current collector of the positive electrode can be an Al foil, or other current collectors commonly used in the art can be used. In some embodiments, the thickness of the current collector of the positive electrode can be from 1 μm to 200 μm. In some embodiments, the positive electrode active material layer can be coated only on a portion of the current collector of the positive electrode.
[0028] In some embodiments, when the electrode is a negative electrode, the active material layer is a negative electrode active material layer. In some embodiments, the negative electrode active material layer includes a negative electrode material, which may include at least one of graphite, hard carbon, silicon, silicon suboxide, or organosilicon. In some embodiments, the negative electrode active material layer may also include a conductive agent. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, Ketjen black, sheet graphite, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the mass ratio of the negative electrode material, conductive agent, and binder in the negative electrode active material layer may be (80 to 98):(0.1 to 10):(0.1 to 10). It should be understood that the above description is merely an example, and any other suitable materials and mass ratios may be used. In some embodiments, the current collector of the negative electrode may be at least one of aluminum foil, copper foil, nickel foil, or carbon-based current collector.
[0029] In some embodiments, the separator comprises at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide, or aramid. For example, polyethylene comprises at least one selected from high-density polyethylene, low-density polyethylene, or ultra-high molecular weight polyethylene. Polyethylene and polypropylene, in particular, are effective in preventing short circuits and can improve battery stability through a turn-off effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 500 μm.
[0030] In some embodiments, the surface of the separator may further include a porous layer disposed on at least one surface of the substrate of the separator. The porous layer comprises inorganic particles and a binder. The inorganic particles are selected from at least one of alumina (Al₂O₃), silicon oxide (SiO₂), magnesium oxide (MgO), titanium oxide (TiO₂), hafnium dioxide (HfO₂), tin oxide (SnO₂), cerium dioxide (CeO₂), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO₂), yttrium oxide (Y₂O₃), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. In some embodiments, the pores of the separator have a diameter in the range of about 0.01 μm to 1 μm. The binder for the porous layer is selected from at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the separator's heat resistance, oxidation resistance, and electrolyte wetting properties, and enhance the adhesion between the separator and the electrode.
[0031] In some embodiments of this application, the electrode assembly of the electrochemical device is a wound electrode assembly, a stacked electrode assembly, or a folded electrode assembly. In some embodiments, the positive and / or negative electrode of the electrochemical device can be a multilayer structure formed by winding or stacking, or a single-layer structure consisting of a single-layer positive electrode, a separator, and a single-layer negative electrode.
[0032] In some embodiments, the electrochemical device includes a lithium-ion battery, but this application is not limited thereto. In some embodiments, the electrochemical device may also include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte solution, wherein the electrolyte solution includes a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, or lithium difluoroborate. For example, LiPF6 is selected as the lithium salt because it has high ionic conductivity and can improve cycle characteristics.
[0033] The non-aqueous solvent may be a carbonate compound, a carboxylic acid ester compound, an ether compound, other organic solvents, or a combination thereof.
[0034] Carbonate compounds can be chain carbonate compounds, cyclic carbonate compounds, fluorocarbonate compounds, or combinations thereof.
[0035] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), or combinations thereof. Examples of fluorinated carbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0036] Examples of carboxylic acid ester compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonic acid lactone, caprolactone, methyl formate, or combinations thereof.
[0037] Examples of ether compounds are dibutyl ether, tetraethylene dimethyl ether, diethylene dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or combinations thereof.
[0038] Examples of other organic solvents include dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters or combinations thereof.
[0039] In some embodiments of this application, taking a lithium-ion battery as an example, the positive electrode, separator, and negative electrode are sequentially wound or stacked to form an electrode assembly, which is then encapsulated in, for example, an aluminum-plastic film. Electrolyte is injected, and the assembly is formed and encapsulated to produce a lithium-ion battery. The prepared lithium-ion battery is then subjected to performance testing.
[0040] Those skilled in the art will understand that the methods for preparing the electrochemical devices (e.g., lithium-ion batteries) described above are merely examples. Other methods commonly used in the art can be employed without departing from the disclosure of this application.
[0041] Embodiments of this application also provide electronic devices including the electrochemical devices described above. The electronic devices in the embodiments of this application are not particularly limited and can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, laptops, pen-based computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium / sodium-ion capacitors, etc.
[0042] The following are some specific embodiments and comparative examples to better illustrate this application, wherein a lithium-ion battery is used as an example.
[0043] Preparation of the positive electrode: Aluminum foil is used as the current collector of the positive electrode. The positive electrode active material lithium cobalt oxide, conductive agent conductive carbon black and binder are dissolved in N-methylpyrrolidone (NMP) solution in a weight ratio of 98.2:0.5:1.3 to form a slurry of positive electrode active material layer. The slurry is coated on the current collector to obtain the positive electrode active material layer. After drying, cold pressing and cutting, the positive electrode is obtained.
[0044] Preparation of the negative electrode: Graphite, conductive agent, and binder were dissolved in deionized water at a weight ratio of 97.8:0.5:1.7 to form a negative electrode slurry. A 10μm thick copper foil was used as the current collector for the negative electrode. The negative electrode slurry was coated onto the current collector, dried, and cut to obtain the negative electrode.
[0045] Preparation of the separator membrane: The separator membrane substrate is 8μm thick polyethylene (PE) as the separator membrane.
[0046] Preparation of electrolyte: Under an environment with a water content of less than 10 ppm, LiPF6 was added to a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC) = 50:50, weight ratio), the concentration of LiPF6 was 1.15 mol / L, and the mixture was stirred evenly to obtain the electrolyte.
[0047] The preparation of lithium-ion batteries: the positive electrode, the separator, and the negative electrode are in close contact in sequence and are stacked to obtain a battery cell. The battery cell and the electrolyte are sealed together in a soft bag and placed in a mold with a certain curvature to be pressed and bent to obtain an arc-shaped battery.
[0048] Test method:
[0049] Film tensile test:
[0050] The adhesive or thermoplastic polymer emulsion was placed on a horizontal glass plate and allowed to air dry for 24 hours. It was then dried in a 60°C oven to constant weight to obtain a film. This film was cut into dumbbell-shaped standard samples using a dumbbell-shaped cutter. Tensile testing was performed using a universal electronic tensile testing machine. The film was held at 100% fixed elongation for 10 minutes, and the load was immediately released, allowing it to recover freely for 10 minutes. The residual deformation was measured, and the 100% tensile permanent deformation was calculated.
[0051] Electrode bending test:
[0052] The electrode slurry was evenly applied to the current collector. After the electrode dried, it was wrapped around a cylinder with a diameter of 2 cm and bent for 5 seconds. The number of cracks on the surface of the electrode was observed and recorded using a CCD camera.
[0053] Curvature rebound rate test:
[0054] The positive electrode, separator, and negative electrode are made into battery cells by winding or stacking. They are then sealed together with the electrolyte in a soft bag and hot-pressed and bent using a convex and concave mold. The curvature test is performed using a surface 3D profilometer to record the change in the radius of curvature of the curved battery before and after 48 hours of rest, and the springback rate is calculated.
[0055] Cyclic performance test:
[0056] The activated arc-shaped battery was placed in a test fixture and clamped. Charge-discharge cycle tests were performed in a 25°C constant temperature chamber with a charge-discharge voltage range of 3.0V to 4.5V. The battery was charged at a rate of 1.2C to 4.5V, then charged at a constant voltage of 4.5V to 0.02C and allowed to stand for 10 minutes. The battery was then discharged at a rate of 0.5C to 3V. This charge-discharge cycle was repeated 400 times. The initial capacity and the capacity after the 400th cycle were recorded. The ratio of the capacity after the 400th cycle to the initial capacity was used as the capacity retention rate.
[0057] The differences between the various embodiments lie in the binder. Specific binder types and components are shown in the table below. Bending tests were performed on the negative electrode sheets of Examples 1 to 13 and Comparative Examples 1 to 3 according to the above test methods, and the number of cracks after the negative electrode sheet was wound around a 2cm diameter cylinder was recorded. Curved battery springback rate and cycle performance tests were conducted, and the springback rate and cycle capacity retention rate were calculated.
[0058] Table 1
[0059]
[0060]
[0061] Wherein, " / " indicates none, CMC is carboxymethyl cellulose, PAA is acrylic polymer, SBR is styrene-butadiene emulsion, and EVA is ethylene vinyl acetate copolymer.
[0062] The difference between Examples 1 and 2 lies in the different types of thermoplastic polymers. In Examples 3 to 5, the types and mass percentages of the bonding polymer and thermoplastic polymer are the same, the only difference being the degree of crystallinity of the thermoplastic polymer. In Examples 6 to 8 and Comparative Examples 1 to 3, the mass percentages of thermoplastic polymers are different, and the 100% tensile permanent deformation of the binder is different. The difference between Examples 9 to 12 lies only in the different radii of curvature. In Example 13, different bonding polymers and thermoplastic polymers were used.
[0063] Comparing Examples 1 to 13 with Comparative Examples 1 to 3, it can be seen that the curvature rebound rate of the lithium-ion batteries in Examples 1 to 13 is lower than that in Comparative Examples 1 to 3, and the capacity retention rate after 400 cycles is higher than that in Comparative Examples 1 to 3. The binder obtained by combining the bonding polymer and thermoplastic polymer used in the examples of this application has a large amount of permanent deformation, and the surface of the electrode sheet produced is crack-free after bending. In contrast, the binder in Comparative Examples 1 and 2 without added thermoplastic polymer has an elongation rate of less than 100%, insufficient plasticity, and the surface of the electrode sheet cracks after being wound around a 2cm diameter cylinder, with a large number of cracks. The binder in Comparative Example 3 without added thermoplastic polymer has a small amount of permanent deformation, resulting in a higher curvature rebound rate of the battery. Compared with Comparative Examples 1 to 3, the curvature rebound rate of the batteries in Examples 1 to 11 is reduced. Compared with Comparative Example 2, even when the battery cell is bent with a curvature radius of 50mm, the battery in Example 12 still has a low curvature rebound rate and a high capacity retention rate of 94%. It can be seen that the addition of thermoplastic polymers in the binder in the range of 0.5% to 50% can effectively increase the permanent deformation of the binder to 50% to 100%, thereby ensuring that the curvature rebound rate of the arc battery made using the electrode sheet described in this application is below 5%, and the larger the curvature radius of the arc battery, the lower its curvature rebound rate.
[0064] As can be seen from Examples 3 to 5, the crystallinity of thermoplastic polymers affects the curvature rebound rate and cycle performance of arc batteries. When the crystallinity is no more than 50%, the overall performance is better.
[0065] As can be seen from Examples 6 to 8, increasing the mass percentage of thermoplastic polymer increases the 100% tensile permanent deformation of the adhesive. This is because increasing the content of thermoplastic polymer improves the plasticity of the adhesive, resulting in smaller changes in curvature rebound rate and cycle performance. However, if the mass percentage of thermoplastic polymer is too high, it will lead to insufficient adhesive force of the adhesive. Therefore, it is necessary to control the mass percentage.
[0066] As can be seen from Examples 9 to 12, when the radius of curvature of the electrode is in the range of 25mm to 200mm, the batteries proposed in this application can all have good performance. As can be seen from Example 13, when the radius of curvature is 5mm, the curvature rebound rate of the arc battery is only 2.6%, and the capacity retention rate after 400 cycles still reaches 92.8%, showing good cycle performance. It can be seen that the embodiments proposed in this application can meet the requirements for arc batteries while ensuring cycle performance.
[0067] As can be seen from the above embodiments and comparative examples, the electrode sheet described in this application can maintain the electrode integrity and cycle performance of the arc battery during high curvature bending and use. The arc battery electrode sheet of this application improves its plastic deformation capability by limiting the composition of the binder, and can generate a larger amount of permanent deformation when the electrode sheet is bent, thereby effectively reducing the curvature rebound of the arc battery.
[0068] The above description is merely a selection of preferred embodiments of this disclosure and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in the embodiments of this disclosure is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the above-described inventive concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features with similar functions disclosed in the embodiments of this disclosure.
Claims
1. An electrochemical device comprising an electrode, the electrode including a current collector and an active material layer located on at least one side of the current collector; the active material layer comprising an active material and a binder, characterized in that, The binder includes a bonding polymer and a thermoplastic polymer, and the radius of curvature R of the electrode sheet is 50 mm to 200 mm; The bonding polymer includes at least one of styrene-butadiene emulsion, carboxymethyl cellulose, or polyacrylic acid; the thermoplastic polymer includes ethylene-vinyl acetate copolymer.
2. The electrochemical device according to claim 1, characterized in that, The radius of curvature R of the electrode is 50 mm to 100 mm.
3. The electrochemical device according to claim 1, characterized in that, The thermoplastic polymer satisfies at least one of the following conditions: The crystallinity of the thermoplastic polymer is less than 50%; The weight-average molecular weight of the thermoplastic polymer is 5,000 to 80,000. The thermoplastic polymer has an elongation at break of 100% to 500%.
4. The electrochemical device according to claim 1, characterized in that, Based on the total mass of the adhesive, the thermoplastic polymer in the adhesive has a mass percentage content of 0.5% to 50%.
5. The electrochemical device according to claim 4, characterized in that, The electrode is a positive electrode, and the thermoplastic polymer has a mass percentage content of 0.5% to 10% in the binder.
6. The electrochemical device according to claim 4, characterized in that, The electrode sheet is the negative electrode, and the thermoplastic polymer has a mass percentage content of 1% to 50% in the binder.
7. The electrochemical device according to claim 1, characterized in that, The tensile permanent deformation of the adhesive is 50% to 100%.
8. An electronic device comprising an electrochemical device according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-flexibility electrode assembly and battery cell comprising same
CN108140873A
Electrode for lithium ion secondary battery
JP2011060559A